Comparison of prognostic prediction between nomogram based on lymph node ratio and AJCC 8th staging system for patients with resected pancreatic head carcinoma: a SEER analysis - Pu, Ning (Cancer Manag Res, 2018)
BACKGROUND: The prognosis of pancreatic carcinoma (PC) remains poor and the American Joint Committee on Cancer (AJCC) 8th staging system for survival prediction in PC patients after curative resection is still limited. Thus, the aim of this study is to refine a valuable prognostic model and novel staging system for PC with curative resection. METHODS: The data of 3,458 patients used in this study were retrieved from the Surveillance, Epidemiology, and End Results database registry of National Cancer Institute. The prognostic value of lymph node ratio (LNR) was analyzed in the primary cohort and prognostic nomogram based on the LNR was established to create a novel staging system. Then, analyses were conducted to evaluate the application of the formulated nomogram staging system and the AJCC 8th staging system. The predictive performance of model was further validated in the internal validation cohort. RESULTS: Significant positive correlations were found between LNR and all factors except for surgical procedures. The results of univariate and multivariate analyses showed that LNR was identified as an independent prognostic indicator for overall survival (OS) in both primary and validation cohorts (all P < 0.001). A prognostic nomogram based on the LNR was formulated to obtain superior discriminatory abilities. Compared with the AJCC 8th staging system, the formulated nomogram staging system showed higher hazard ratios of stage II, III, and IV disease (reference to stage I disease) that were 1.637, 2.300, and 3.521, respectively, by univariate analyses in the primary cohort and the distinction between stage I, II, and III disease at the beginning or end of the survival curves was more apparent. All these results were further verified in the validation cohort. CONCLUSION: LNR can be considered as a useful independent prognostic indicator for PC patients after curative resection regardless of the surgical procedures. Compared with the AJCC 8th staging system, the formulated nomogram showed superior predictive accuracy for OS and its novel staging system revealed better risk stratification.